Virtual reality application for stress therapy: Issues and challenges - Zaharuddin, F.A. (2020)
Given that stresshas affected many people and is becoming an important issue to address, the development of an application that can help people to relax and therefore reduce stress is becoming important. One of the solutions is the use of virtual reality (VR) in stress therapy. In this paper, we evaluate a virtual reality application developed for stress therapy, and highlighted the issues associated with such application. Based on the issues, we proposed a component framework which can be used to develop a VR application for stress therapy which provides holistic experience to the users. ©BEIESP.